Russian higher education problems through the comparative analysis of journal publications from 2011 to 2012 - Galina I. Saganenko (Высшее образование в России)
Our task consists in finding specific features of a social situation with Russian higher education through a certain resource of problems actualization. Namely, the substantial subjects of two full arrays of titles of the articles of the «Higher Education in Russia» journal relating to 2011 and to 2012 are considered in the comparative coordinates. The authors of these publications are mainly the teachers in higher education institutions, respectively, through the representations of this category of people it is possible to reveal the significant problems of Russian education.The title of the publication, which usually contains the keywords, can be viewed as the mostcondensed form of its summary. The analyzed sets contain, respectively, 291 and 262 single titles of publications, in these sets there were used 1728 and 1530 words, an each set contained 671 and 587«unique» words, respectively.The work was carried out with information arrays within the analytical modules of the “VEGA” computer program providing creation of databases, a set of ways of texts systematization, qualitative and quantitative analysis, convenient dictionaries. Permutation, alphabetic and frequency dictionaries were used.This work was carried out for the purpose of comparison of two «social products» - two annual information arrays of the journal titles for revealing of significant social characteristics of modern Russian education. The analysis of the themes and focuses of authors’ attention shows how an academic community treats the situation in Russian education.